The impact of Bologna process on the graduate labour market: Demand and supply - Giulio Bosio; Marco Leonardi (Institute for the Study of Labor (IZA), 2011)
The Bologna process inspired the Italian 3+2 reform of the university system which constitutes a big increase in the supply of college graduates. This paper is a preliminary attempt to identify the effects of the reform on (i) the relative probability (relative to non-graduates) of employment of college graduates in the age range 25-34; (ii) their quality of employment measured with the relative probability of being employed with a temporary contract; (iii) the college wage premium. Using administrative data to identify the gradual introduction of the reform in different universities, we find that the reform increases significantly the relative employment of graduates except for women in the South where the rapid increase of female post-reform graduates has not been absorbed by the weak labour market. Finally we find that post-reform college graduates have a significantly lower college premium with respect to high school graduates than pre-reform graduates.
urn:nbn:de:101:1-201106224691
Keywords: I23; I28; J24; 330; university reforms; college attainment; college wage premium